Vascular access for isolated hepatic perfusion in liver metastases. Place of artificial circulation. Literature review - V. M. Unguryan; A. N. Kazantsev; Y. V. Belov (Российский кардиологический журнал)
The use of an artificial circulation and endovascular technologies in the treatment of liver metastases of uveal melanoma is a highly relevant area. Uveal melanoma is a rare cancer from the uveal tract of the eye. The liver is the most common site of metastasis and is affected in 70-90% of cases, being the only site of metastasis in about 50% of cases. Survival ranges from two to three months. This literature review describes the following methods of treatment of liver metastases of uveal melanoma using a heart-lung machine: arterial (arterio-caval), portal (porto-caval), arterio-porto-caval, retrograde arterio-portal. Special attention is paid to the endovascular method of treatment.Literature sources were searched in the following electronic libraries: elibrary.ru, pubmed.ncbi.nlm.nih.gov, researchgate.net.